Correlation of clinical parameters with endolymphatic hydrops on MRI in Meniere's disease - Han, Seung Cheol; Kim, Young Seok; Kim, Yehree; Lee, Sang-Yeon; Song, Jae-Jin; Choi, Byung Yoon; Kim, Ji-Soo; Bae, Yun Jung; Koo, Ja-Won (Frontiers in Neurology, 2022)
A clinical diagnosis of Ménière's disease (MD) is made based on medical history and audiometry findings. The 1995 American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) guidelines requires histopathological confirmation of endolymphatic hydrops (EH) for a diagnosis of “certain” MD. Symptoms such as dizziness and ear fullness are important diagnostic features; however, the descriptions provided by patients are frequently vague and non-specific. A recently developed magnetic resonance imaging (MRI) protocol to document EH is, therefore, useful for the evaluation of inner ear status in patients with MD. In this study, patients with MD were assessed using MRI and the HYDROPS (HYbriD of Reversed image Of Positive endolymph signal and native image of positive perilymph Signal) protocol to investigate the effectiveness of MRI for visualization of the endolymphatic space in the diagnosis of MD by correlating clinical laboratory parameters with the grade of EH. Of the 123 patients with MD recruited in this study, 80 had definite MD, 11 had probable MD, and 32 had possible MD based on the 1995 AAO-HNS guidelines. The EH grade based on HYDROPS MRI was determined independently by two otorhinolaryngologists and compared with several clinical parameters, including the diagnostic scale of MD (1995 AAO-HNS guidelines), pure tone average (PTA), low tone average (LTA), canal paresis (CP) on the caloric test, and disease duration. Cochlear hydrops and vestibular hydrops were detected in 58 and 80% of 80 definite MD ears, in 33 and 58% of 12 probable MD ears, and in 5 and 27% of 37 possible MD ears, respectively. The proportion of higher hydrops grades increased significantly with grade according to the MD diagnostic scale (p < 0.0001). Both PTA and LTA were significantly higher in patients with hydrops grade 2 than hydrops grade 0 in both the cochlea and the vestibule. CP was significantly higher in patients with grade 2 than grade 0 vestibular hydrops. Disease duration was not associated with hydrops grade. Radiological evaluation of MD using the HYDROPS protocol is useful for evaluation of the extent and severity of EH in the diagnosis of MD based on its pathophysiological mechanism.